2017
DOI: 10.4014/jmb.1609.09043
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm and Anti-��-Lactamase Activities of Burdock Root Extract and Chlorogenic Acid against Klebsiella pneumoniae

Abstract: Small phytochemicals have been successfully adopted as antibacterial chemotherapies and are being increasingly viewed as potential antibiofilm agents. Some of these molecules are known to repress biofilm and toxin production by certain bacterial and yeast pathogens, but information is lacking with regard to the genes allied with biofilm formation. The present study was performed to investigate the inhibitory effect of burdock root extract (BRE) and of chlorogenic acid (CGA; a component of BRE) on clinical isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 37 publications
0
24
1
Order By: Relevance
“…Staphylococcus aureus biofilms are important in chronic and persistent mastitis infections and can cause bacterial resistance to treatment with antimicrobial agents (Melchior et al, 2006). A previous study demonstrated that CGA could significantly repress biofilm formation in the context of persistent Klebsiella pneumoniae infection (Rajasekharan et al, 2017). Although statistical significance was not reached, our results suggest a trend for the reduction of biofilm with CGA treatment in BMEC cultures challenged with S. aureus.…”
Section: Discussioncontrasting
confidence: 62%
“…Staphylococcus aureus biofilms are important in chronic and persistent mastitis infections and can cause bacterial resistance to treatment with antimicrobial agents (Melchior et al, 2006). A previous study demonstrated that CGA could significantly repress biofilm formation in the context of persistent Klebsiella pneumoniae infection (Rajasekharan et al, 2017). Although statistical significance was not reached, our results suggest a trend for the reduction of biofilm with CGA treatment in BMEC cultures challenged with S. aureus.…”
Section: Discussioncontrasting
confidence: 62%
“…Again, the plates were incubated statically under the same conditions of time and temperature. Then, the same process described above was performed before evaluation with a microplate spectrophotometer [ 46 ]. Statistical significance was determined by pair-wise testing using the Student’s t-test, and the results were considered statistically significant when p < 0.05 for the rejection of the null hypothesis.…”
Section: Methodsmentioning
confidence: 99%
“…Chlorogenic acid (CA), one of the most common polyphenol compounds, is abundant in coffee beans, and also exist in various vegetables and fruits . Studies have revealed that CA has pharmacological activities against bacteria, inflammation and oxidation, as well as hyperlipidemia disease . In addition, several studies showed that CA shows anticancer properties.…”
Section: Introductionmentioning
confidence: 99%